Model Evaluasi Kurikulum Pendidikan: Definisi, Fungsi, Manfaat, dan Penerapan CIPP (Context, Input, Process, Product) - Ade Firdaus; Abdurrahmansyah (CV. Doki Course and Training, 2025)
This study aims to discuss curriculum evaluation, including the definition of curriculum evaluation, the benefits of conducting it, the function of curriculum evaluation, and curriculum evaluation models. The discussion in this article is largely influenced by experts in the field of curriculum evaluation, so the opinions and thoughts of these experts serve as important references in reviewing the discussion.In the conclusion of this discussion, the author found that curriculum evaluation is a systematic effort carried out to improve the curriculum that is still in the development stage or the curriculum that has been implemented so that it is better prepared in the future, curriculum evaluation is beneficial for all parties including teachers, educational stakeholders, parents and the community, curriculum evaluation has formative and summative functions which ultimately have an impact on educational, instructional, diagnostic, and administrative activities., Curriculum evaluation models, including the CIPP Model (Context, Input, Process and Product).